FORMAL AND INFORMAL WOMEN WORKERS: A SYSTEMATIC BIBLIOMETRIC EXPLORATION AND VISUALIZATION OF RESEARCH TRENDS AND THEMES - George, Tessymol; Vipin Chandran K P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This bibliometric analysis explores the research landscape on formal and informal women workers, who engage in organized, regulated employment or unorganized, unregulated sectors, respectively, each characterized by differing levels of job security, social protection, and working conditions. The study employs Biblioshiny and VOSviewer software, using data from the Scopus bibliographic database, to map the academic progress in this domain. The analysis examines Annual Scientific Production, revealing trends in scholarly output over time, and identifies the most relevant authors and sources shaping this field. Geographical insights are provided through an evaluation of countries’ scientific production and co-authorship networks, emphasizing the global distribution of research efforts. Trend topics showcase the evolution of thematic priorities, while the thematic map highlights central and emerging themes in the literature. Bibliographic coupling of documents uncovers intellectual connections between studies, and keyword co-occurrence analysis sheds light on the conceptual framework of the field. The study also investigates collaboration patterns, with a focus on co-authorship at the country level, offering insights into international partnerships. The findings provide a nuanced understanding of the research priorities and gaps in the study of formal and informal women workers. These insights aim to inform policymakers and researchers, facilitating targeted strategies for addressing issues faced by women in both employment sectors.